Michael Recycle - Bethel, Ellie; Colombo, Alexandra (London : IDW & Jonas Pub. ; San Diego, CA : Worthwhile Books, 2008)
Michael Recycle teaches the people of Abberdoo-Rimey, a town where trash is piled high, about recycling their garbage.
1.8
K-3
Keywords: Recycling (Waste, etc.) -- Juvenile fiction; Recycling (Waste) -- Fiction; Recycling -- Fiction; Children's stories -- Pictorial works